Preference of red mite Tetranychus ludeni Zacher (Acari: Tetranychidae) to sweet potato genotypes - B. M. C. Castro; M. A. Soares; V. C Andrade Júnior; V. C. Santos Júnior; P. C. R. Fontes; C. F. Wilcken; J. E. Serrão; J. C. Zanuncio (Brazilian Journal of Biology, 2018)
Abstract Tetranychus ludeni damages the sweet potato. Pest development can vary between plant genotypes. The objective was to identify the preference of Tetranychus ludeni for Ipomoea batatas genotypes, from the germplasm bank at the Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM). Natural infestations of this mite were observed on 54 sweet potato genotypes in potted, in a greenhouse. Three mite-infested leafs of each genotype were collected and analyzed. The red mite showed different population density rate in genotypes. The BD 29 genotype was found to be highly susceptible, the BD 08, BD 57, BD 17 and Espanhola genotypes were moderately susceptible, and the others forty-nine genotypes showed low susceptibility to the mite.